Compassionate mind training for university students – A randomized controlled trial - Christina Andersson; Siri Jakobsson Støre; Helena Säldebjer; Mika Gunnarsson; Katja Lindert Bergsten; Walter Osika (Acta Psychologica)
The study objective was to assess the effects of a five-week compassionate mind training for university students regarding symptoms of depression, anxiety and stress, and self-compassion compared with an active control group. Swedish university students were randomized to a compassionate mind training group or to an active control group. The outcome measures were.the Hospital Anxiety and Depression scale, the Perceived Stress Scale 14, and the Self-Compassion Scale – Short Form. All outcomes were measured pre- and post-intervention. Data were analyzed with linear mixed-effects models. The only statistically significant difference between the groups were depression symptoms (p = 0.02, d = −0.40) corresponding to a slight clinically relevant improvement. The study's results are consistent with prior research suggesting that compassionate mind training may be beneficial for alleviating depression symptoms. However, the low baseline depression levels in this sample and the short duration of the intervention may limit the generalizability and the magnitude of the findings. The small sample size and relatively homogenous group, also point to the need for larger and more diverse samples.